Mimesis de la douleur chez George Oppen et J. H. Prynne - Xavier Kalck (Sillages Critiques)
This article means to consider the work of two poets working in the second half of the twentieth century - an American, George Oppen, and a British poet, J. H. Prynne - and how they resort to quotation as a technique when dealing with expressions of pain. The aim is to attempt a practical application of Wittgenstein’s remarks on learning language using the example of expressions of pain. Are such quotations a means for these authors to bring back a measure of subjectivity within the textual pattern, and if so why? The question matters all the more as the poems do not partake of collage as the belated sign of modernist claims. The issue is that of one’s connection to the existing world and how this connection must be maintained and the world accounted for.